DEFENSE POLICIES OF EAST-CENTRAL EUROPEAN COUNTRIES AFTER 1989 creating stability in a... time of uncertainty. - PETERSON, JAMES W.. LUBECKI, JACEK (MANCHESTER UNIV PRESS, 2020)
"The 2014 Ukrainian-Crimean crisis has raised serious questions in the West about Russian motivations and future policy directions. Now more than ever, it is imperative to explore the defensive perceptions, reactions, and preparations of neighboring countries-- the Czech Republic, Hungary, Poland, and Slovakia. Is there a convergence of their approaches along similar paths, or do their different cultures and historical experiences prefigure a divergence of their defense policies? While Slovakia, Hungary and the Czech Republic all seem to have little concern about Russia's policies in Ukraine, the Polish response has been uniquely strong and militarized. This book will explore reasons for the different responses to the crisis"--